Optimization of S-EDM Process Parameters on Material Removal Rate using Copper Electrodes - Khoirudin Khoirudin; Sukarman Sukarman; Nana Rahdiana; Ade Suhara; Ahmad Fauzi (Jurnal POLIMESIN, 2023)
This article demonstrates that the sinker electrical discharge machining (S-EDM) method can be enhanced using SPHC (JIS G 3131) materials with a hardened surface. During S-EDM, neither contact nor a cutting force exists between the electrode and the workpiece. S-EDM is advantageous because it eliminates mechanical stress, chatter, and vibration issues with traditional milling. S-EDM is widely employed, for example, in the manufacturing of molds for automotive and aviation components. Taguchi design and signal-to-noise ratio (S/N ratio) were selected to examine the impact of the input parameter model on the material removal rate (MRR). The Taguchi approach assessed three input parameters and three experimental levels. The parameters pulse current (I), spark time (Ton), and gap voltage (Vg) were chosen to evaluate the MRR performance of the S-EDM process with the SPHC-hardened workpiece material. Copper with a diameter of 10 mm is chosen as the electrode material. This study aims to determine the optimal MRR for the chosen input variables. Results indicate that a more effective pulse current value promotes debris removal from the machining zone and stabilizes following spark release, speeding the material removal rate (MRR). In the S-EDM machining process, the pulse current value significantly affects the MRR and is one of the most significant response variables